การศึกษาวิเคราะห์วรรณกรรมการแปลคัมภีร์อัลกุรอานฉบับภาษาไทยด้านหลักศรัทธาต่อพระนามและคุณลักษณะของอัลลอฮฺ - นุชมี, อดิศักดิ์; การีนา, อับดุลเลาะ (Al-HIKMAH Journal, 2018)
The Thesis, “An Analytical Study of Literary Translation of the Thai Version of the Holy al-Qur‘an Regarding the Faith Toward Names and Characteristics of Allah”, has objective to investigate and analyse fundamental belief of the targeted group scholars who worked on Thai translation of the Holay al-Qur‘an. The analysis is conducted base on their interpretation discipline regarding name and characteristics of Allah in their versions. In addition to the main objective, this thesis examines factors that influence each translator toward theire idiaological of Salaf and Kolaf. As for this thesis is a qualitative research method was implemented using data from historical papers and target group Interview. The result found that the versions of Tuan Suvannasat is respectively the most according to Kolafism and Winai Samaun Was Seconded On the other hand, the version of the Arab university alumni association is the most according to Salafism and the Direk Kulsirisawat version was seconded. The difference in interpretation of the words by each translator toward Kolaf and Salaf theology is happened base on the influence of two factors, (1) their variety of education, background knowledge, and faith together with (2) the variety of reference texts used by the author of each translation version. It can be concluded that education background, knowledge and faith influence scholars to select the references in according to their fundamental belief.